Hybrid fuzzy-PID bidirectional speed controller for BLDC with seamless speed reversal using direct commutation switching scheme - Satishrao, Pothorajoo; Hamdan, Daniyal (UTeM, 2018)
Brushless Direct Current (BLDC) motors have attracted a lot of attention due to their performance capabilities. The Proportional Integral (PID) controller remained popular due to its simplicity. However, PID’s performance deteriorates during nonlinear loads conditions. Controllers have been developed to overcome the limitations of the PID controllers but focused on forwarding motor only. Furthermore, lack of literature regarding the bidirectional speed control of BLDC motor has been reported. In this paper, a Hybrid Fuzzy-PID speed controller for BLDC with seamless speed reversal using direct commutation switching scheme was proposed. The controller uses Fuzzy rule base and the switching scheme for bidirectional operations. MATLAB/Simulink was used to develop and test the controller. The controller was tested for several test cases and compared to a ZN-Tuned PID controller. The controller performed efficiently for all the test cases and has better results compared to the PID controller under same test cases.